Hubungan Tingkat Pengetahuan Perawat terhadap Penerapan Patient Safety Di Ruang IGD RSD Gunung Jati Kota Cirebon Tahun 2020 - Idris Handriana; Epon Yuningsih (Syntax Corporation Indonesia, 2021)
Patient safety has become a global issue for hospitals, a top priority to be implemented, and is a something far more important than jus service efficiency, it is related ti the issue of the quality and image of the hospital. This study was conducted with the aim to determine the relationship of the level of knowledge of nurses to the appication of patient safety in the Emergency Room of Gunung Jati Hospital Cirebon City in 2020. This research was a descriptive study with cross sectional approach. The number of samples using a total sampling thechnique of 30 nurses with a questionnaire research instrument. The independent variable covered nurses knowledge about patient safety. Dependent variable includes the application of patient safety by nurses. The level of nurses knowledge of patient safety in Emergency Room RSD Gunung Jati Cirebon City in 2020, most (80%) of respondents had a good level of knowledge about patient safety. The application of patient safety in Emergenci Room RSD Gunung Jati Cirebon City in 2020, most (86,7%) respondents did the application of patient safety well. There is a relationship between the level of nurses knowledge on the application of patient safety in the Emergenci Room RSD Gunung Jati Cirebon City in 2020, р (0.002). The results of the study can be input to medical nurses to learn more about patient safety knowlegde, so that increasing nurses knowledge about patient safety can prevent medical errors in work.